MODIFIKASI SERAT ALAM DAN KARAKTERISASINYA SEBAGAI PENGUAT MATERIAL KOMPOSIT - Umi Lailatul Jamilah; Elok Hidayah (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
Environmental concerns have influenced a number of researchers to develop nature-based composite materials. These composite materials are composed of fibers and matrix, which are partially or completely derived from nature. Natural fibers are widely applied to reduce the utilization of synthetic fibers. However, natural fibers have hydrophilic properties that make it difficult to interact with the matrix, which tends to be hydrophobic. This condition results in the weak mechanical strength of natural fiber-reinforced composite materials. It is necessary to modify the surface of natural fibers, so that the interaction between natural fibers and the matrix can be improved, so that the resulting mechanical strength also increases. A number of analyses on natural fiber surface modification are discussed in this article to discuss the effect of each natural fiber surface modification method, as well as its characteristics when applied as reinforcement in composite materials. The analysis in this article includes several modification methods such as: alkalization, silane, and acetylation, as well as composite mechanical characteristics such as: tensile strength and elastic modulus. The analysis process is carried out by collecting several reference sources from books, and scientific articles accredited by national or international journals. Among the three methods analyzed, alkalization is the most widely applied method for natural fiber surface modification.